IMPROVING YOUNG LEARNERS’ INTEREST IN READING - Dewi, Anak Agung Istri Bulan Fitria; Prawita, Ni Ketut Riska Dewi (Yavana Bhasha : Journal of English Language Education, 2019)
The aim of this study is to enhance the young learners to make them interest in reading the books by several methods. These methods may help to increase the self-interest in reading. In globalization era, the development of the teaching and learning of English has been transformed. Nowadays, learners should not only focus on the learning of speaking and writing but also reading due to requirements of education that they should be able to understand and respond to the texts. There are many reasons the young learners have less interesting in reading, for example the development of the information forces the focus of teaching and learning on the critical reading. The most common thing is the students may not know their interest in reading before they start to read the books. Reading interests play a very important role in reading instruction and improvement. Furthermore, the understanding of young learners’ interest and abilities is required to help them in reading. This article entitled Improve Young Learners’ Interest in Reading consists of the great way of method to encourage the young learners to read through the use of wall magazine, the use of flash card, and the use of humor that can applied in strategies of reading aloud, reading the book several times, reading favorite books, and show many picture books.